2011
DOI: 10.1002/ppul.21539
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitivity C reactive protein as a biomarker for grading of childhood asthma in relation to clinical classification, induced sputum cellularity, and spirometry

Abstract: Despite that pulmonary function tests and clinical classification are the gold standard for grading of asthma, hs-CRP can be considered as a new marker for assessment of different grades of asthma severity and control. It can be used for indirect detection and monitoring of airway inflammation, disease severity, and response to steroid treatment in asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
3
41
0
1
Order By: Relevance
“…The intensity of the systemic inflammation rises during exacerbations of asthma. Increased proinflammatory cytokines such as CRP, TNF-α, and IL-6 are elevated during asthma exacerbations [3,4]. Furthermore, IL-6 influences megakaryocyte ploidy and platelet volumes [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the systemic inflammation rises during exacerbations of asthma. Increased proinflammatory cytokines such as CRP, TNF-α, and IL-6 are elevated during asthma exacerbations [3,4]. Furthermore, IL-6 influences megakaryocyte ploidy and platelet volumes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that systemic inflammation is related to disease progression in asthma [2]. Some proinflammatory cytokines such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, and C-reactive protein (CRP) are increased in patients with asthma [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric population, CRP has been utilized in diseases such as Kawasaki disease [13], asthma [14], appendicitis [15], and neonatal sepsis [16]. Recently, an elevation of the CRP has been noted in children with SCD during episodes of vasoocclusive crisis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in proinflammatory cytokines, such as interleukin-6 [6] and tumor necrosis factor-α [7,8] have already been described in asthmatic patients as well as elevated circulating C-reactive protein levels in non-allergic [9], and neutrophilic asthma [10]. In steroid-naive asthmatic patients Creactive protein levels negatively correlated with indices of lung function (forced expiratory volume in one second (FEV1), FEV1/ forced vital capacity and forced mid-expiratory flow) and positively with sputum eosinophil count [11].…”
Section: Introductionmentioning
confidence: 97%